Immersive Virtual Reality in Primary Education: A Systematic Literature Review on 21st Century Learning Integration - Laksmi Evasufi Widi Fajari; Moh Salimi; Ratna Hidayah; Neza Agusdianita; Banu Setyo Adi; Tarma Tarma; Hasan Zainurri (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to review recent empirical studies on the use of Virtual Reality (VR) in primary education, with particular attention to how different levels of immersion contribute to 21st-century learning. Methodology: This study followed PRISMA guidelines for a systematic literature review. Searches were conducted in Scopus, Web of Science, ERIC, ScienceDirect, and Google Scholar using the keywords (“Virtual Reality” OR “VR”) AND (“Primary Education” OR “Elementary School”). A total of 124 records were identified, 12 duplicates were removed, 34 records were screened, and 21 studies were included for final synthesis based on the eligibility criteria (peer-reviewed, 2019–2025, English, primary education context, full text accessible). Data were synthesized through qualitative content analysis by categorizing studies according to VR types (non-immersive, semi-immersive, fully immersive) and reported learning outcomes related to 21st-century skills. Main Findings: The research results indicate that: (1) Non-Immersive VR provides ease of access and use with a learning experience that is still limited to basic interactions; (2) Semi-immersive VR offers a more interactive and immersive learning experience through the use of more realistic simulations and visualizations; and (3) Fully immersive VR was most frequently reported in the reviewed studies and was associated with deeper multisensory engagement, enhanced conceptual understanding, and the development of 21st-century skills in primary education. Novelty/Originality of this study: This study offers a comparative synthesis of non-immersive, semi-immersive, and fully immersive VR in primary education and highlights the pedagogical factors that shape their educational contribution.